Reduced Variation in Drosophila Simulans Mitochondrial DNA - Ballard, JWO. (1996)
We investigated the evolutionary dynamics of infection of a Drosophila simulans population by a maternally inherited insect bacterial parasite, Wolbachia, by analyzing nucleotide variability in three regions of the mitochondrial genome in four infected and 35 uninfected lines. Mitochondrial variability is significantly reduced compared to a noncoding region of a nuclear-encoded gene in both uninfected and pooled samples of flies, indicating a sweep of genetic variation. The selective sweep of mitochondrial DNA may have been generated by the fixation of an advantageous mitochondrial gene mutation in the mitochondrial genome. Alternatively, the dramatic reduction in mitochondrial diversity may be related to Wolbachia.